THE SEVENTEETH CENTURY EDITION: THE STUDY OF VARIANTS IN CORNEILLE'S COMIC ILLUSION - Euphrosyne EFTHIMIADOU (Universitaria Publishing House, Craiova, 2021)
The 17th century is of particular interest because of the authors 'concern to re-edit their works. More specifically, Corneille never ceases to question himself in order to evolve his first theatrical works. Indeed, the poet had his remarkable play, The Comic Illusion, repeatedly reworked, which is characterized by the suppression of verses or even the modification of scenes and of the role of certain characters. In addition, the author highlights the respect of a classical aesthetic, which harmonizes with the concern for sharpness, precision and clarity because the corrections made are related to the rules of propriety. Finally, Corneille is constantly concerned with the stylistic reshuffle, since he cares to reform his style by making it noble and dignified according to the literary requirements of his time, which testifies to his continual renewal.